Improving the Quality of Tourist Services in Central Russia - VAPNYARSKAYA, Olga Igorevna; KRIVOSHEEVA, Tatyana Mikhailovna (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The Central Federal District (CFD) is a core of cultural, educational, and business tourism in the country. The regions of the CFD have a high cultural, educational, tourist, and recreational potential. The historical and cultural experiences of some regions of the north-eastern part of the CFD determine the high rates of tourism development and contribute to the active growth of the hotel property market as well as shopping and entertainment infrastructure. Experts predict further changes in this business that will bring profit and financial success only if novel contemporary routes and developments are introduced.ABSTRACT El Distrito Federal Central (CFD) es un núcleo de turismo cultural, educativo y de negocios en el país. Las regiones del CFD tienen un alto potencial cultural, educativo, turístico y recreativo. Las experiencias históricas y culturales de algunas regiones de la parte noreste del CFD determinan las altas tasas de desarrollo turístico y contribuyen al crecimiento activo del mercado inmobiliario hotelero, así como a la infraestructura de compras y entretenimiento. Los expertos predicen nuevos cambios en este negocio que traerán ganancias y éxito financiero solo si se introducen nuevas rutas y desarrollos contemporáneos.